2D parametric contrast time-density analysis for the prediction of complete aneurysm occlusion at six months' post-flow diversion stent. Issue 4 (August 2020) - Hussein, Ahmed E; Shownkeen, Meghana; Thomas, Andre; Stapleton, Christopher; Brunozzi, Denise; Nelson, Jessica; Naumgart, John; Linninger, Andreas; Atwal, Gursant; Alaraj, Ali
Objective: Indications for the treatment of cerebral aneurysms with flow diversion stents are expanding. The current aneurysm occlusion rate at six months ranges between 60 and 80%. Predictability of complete vs. partial aneurysm occlusion is poorly defined. Here, we evaluate the angiographic contrast time-density as a predictor of aneurysm occlusion rate at six months' post-flow diversion stents. Methods: Patients with unruptured cerebral aneurysms proximal to the internal carotid artery terminus treated with single flow diversion stents were included. 2D parametric parenchymal blood flow software (Siemens-Healthineers, Forchheim, Germany) was used to calculate contrast time-density within the aneurysm and in the proximal adjacent internal carotid artery. The area under the curve ratio between the two regions of interests was assessed at baseline and after flow diversion stents deployment. The area under the curve ratio between completely vs. partially occluded aneurysms at six months' follow-up was compared. Results: Thirty patients with 31 aneurysms were included. Mean aneurysm diameter was 8 mm (range 2–28 mm). Complete occlusion was obtained in 19 aneurysms. Younger patients ( P  = 0.006) and smaller aneurysms ( P  = 0.046) presented higher chance of complete obliteration. Incomplete occlusion of the aneurysm was more likely if the area under the curve contrast time-density ratio showed absolute ( P  = 0.001) and relative percentage ( P  = 0.001) decrease after flow diversion stents deployment. Area under ROC curve was 0.85. Conclusion: Negative change in the area under the curve ratio indicates less contrast stagnation in the aneurysm and lower chance of occlusion. These data provide a real-time analysis after aneurysm treatment. If validated in larger datasets, this can prompt input to the surgeon to place a second flow diversion stents.